If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 9(y + 10) + 2 = 0 Reorder the terms: 2 + 9(10 + y) + 2 = 0 2 + (10 * 9 + y * 9) + 2 = 0 2 + (90 + 9y) + 2 = 0 Reorder the terms: 2 + 90 + 2 + 9y = 0 Combine like terms: 2 + 90 = 92 92 + 2 + 9y = 0 Combine like terms: 92 + 2 = 94 94 + 9y = 0 Solving 94 + 9y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-94' to each side of the equation. 94 + -94 + 9y = 0 + -94 Combine like terms: 94 + -94 = 0 0 + 9y = 0 + -94 9y = 0 + -94 Combine like terms: 0 + -94 = -94 9y = -94 Divide each side by '9'. y = -10.44444444 Simplifying y = -10.44444444
| 2+8(z+10)+10= | | X^3+9= | | 2x+194=10x-6 | | 2(3j-3)=4 | | 3/x+4=5/x | | -6p-1=5-5p+1 | | 15x/200=50 | | 6y-3-5y=7 | | 3(4-(2))+4(-4)= | | 2x+49=10x-6 | | 6x+12=3x+7x | | 3(4-(2))+4x-4= | | -3(8x+5)=-13(1-2x) | | f(x)=x^2+4x+4(x-1) | | 1/2=16.91+3 | | 4sec^2x-2=0 | | -5x^3-25x^2+30x=0 | | 4+c+c=13 | | -16+(77/-11)=n | | 9x^2+3x+9/3 | | 6n^2-30n=0 | | (16x^17*(2x)^-3)/(x^-3)^-4 | | -3/8=15/y | | y*8482105421215240=656665656566565656656565656656568658 | | 20-x/2=14-x | | 8/y=6 | | l*9=18 | | -13t+2t-5=-16 | | 4(x-2)=2(x-3)+9 | | 34-7x=3x+14 | | 6m+3m+-2=-20 | | 6m+3m+-2=20 |